Clinician behavioural intention to perform screening and brief intervention for alcohol-related injury in the emergency department - Flewellen, R.; Lam, Tina; Carruthers, S.; Dinh, M.; Egerton-Warburton, Diana; Allsop, S. (Wiley-Blackwell Publishing Ltd., 2015)
Introduction and Aims: Alcohol related injury is a major public health challenge, especially in emergency departments (ED). Staff responses may be influenced by a number of factors, including perceptions of people affected by alcohol, confidence about responding and demands on limited resources. It is critical to understand how clinician beliefs might influence effective care. This research aimed to identify attitudes and beliefs associated with responses to alcohol related injury (ARI). Three focus groups (n = 26 participants) and a survey of clinician attitudes and behaviours explored how ED clinicians currently respond to ARI, and identified barriers/facilitators to implementing an evidence-based response. Design and Methods: Following the focus groups an online survey, based upon a Theory of Planned Behaviour framework, explored self-reported attitudes and beliefs towards ARI. It was hypothesised that attitudes towards people who sustain an ARI would influence intention to intervene. Results: Completion rates were high (76%) with 715 surveys submitted. A diverse representation of doctors, nurses and ED allied health staff responded from all Australian States and Territories and New Zealand. The majority worked in a metropolitan/major referral or urban district facility and had recently treated ARI. Discussion and Conclusions: Respondents were divided in their beliefs on whether the ED was practical setting to address harmful alcohol consumption, but most agreed ARIs were time-consuming. Previous research suggested preventive/early interventions for ARI were considered outside the scope of practice despite the fact that dependence or excessive drinking has been implicated in many ED presenting problems. Additional study findings may help explain this challenge.